Diatom communities associated with elevated and variable groundwater salinity in Karoo farm reservoirs, South Africa - M. Holmes; J.C. Taylor; B. Linol (South African Journal of Botany, 2026)

A geodynamic interpretation of the Damara - Dom Feliciano orogen as part of southwest Gondwana using Landsat8 Operational Land Imager satellite imagery - K.S. Winkler; B. Linol; C.M. Doucouré (Journal of Structural Geology, 2026)

The demise of an icehouse: Calibrating the end of the LPIA - N. Griffis; R. Mundil; I.P. Montañez; P. Dietrich; D. Le Heron; R. Iannuzzi; B. Linol; T. Mottin; J. Richey; C. Kettler (Global and Planetary Change, 2025)

Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.